Terapia anty-VEGF w leczeniu neowaskularyzacji plamkowej towarzyszącej krótkowzroczności – opis przypadków - Figurska, Małgorzata; Stankiewicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: Myopia is the second most frequent cause of CNV after AMD. Since the introduction of verteporfin photodynamic therapy and anti-angiogenic drugs into clinical practice, major changes occurred in the treatment of subfoveal exudative maculopathy associated with myopia.The aim of the paper is to present the effect of intravitreal injections ranibizumab (Lucentis) for myopic choroidal neovascularization . Material and methods: The study included two patients (25 and 55 years old women) with high myopia. Diagnosis and monitoring of the treatment were based on fluorescein angiography and optical coherence tomography. Results: In 55-years old woman after two injections central retinal leakage decreased in fluorescein angiography and optical coherence tomography and visual acuity improved of two lines(10letters). After 9months follow-up in 25 years old woman`s after three injections of Lucentis, visual acuity improved of three lines on ETDRS chart (15 letters). The leakage in fluorescein angiography was closed. Conclusions: Intravitreal injections therapy of ranibizumab may be a therapeutic option for CNV associated with myopia. It causes chance for decreased central retinal thickness and increased visual acuity, particularly in view of the young patients. One must take note of the other illness associated with CNV in myopic eyes like as epiretinal membranes or vitreoretinal tractions.